MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA SMA KELAS XI MENGGUNAKAN PENDEKATAN PEMBELAJARAN BERBASIS MASALAH PADA MATERI LINGKARAN - Hamka, Muhamad; Jalaludin, Muhamad; Rohaeti, Euis Eti; Afrilianto, M (IKIP Siliwangi, 2018)
This study aims to examine and analyze about problem based learning approach to improve understanding ability in senior high school . The population in this research is XI IPA grade senior high school in Karawang. This study was designed qualitative descriptive method. Based on the results and discussion students understanding ability had improved. Based on the results of the analysis and discussion, it can be concluded that students' mathematical understanding on the subject matter